Answer:
x = 19
Explanation:
Assuming the question was (5x + 4)° (8x – 71)°=180° not (5x + 4)° (8x – 710°,
Simplifying
(5x + 4) + (8x + -71) = 180
Reorder the terms:
(4 + 5x) + (8x + -71) = 180
Remove parenthesis around (4 + 5x)
4 + 5x + (8x + -71) = 180
Reorder the terms:
4 + 5x + (-71 + 8x) = 180
Remove parenthesis around (-71 + 8x)
4 + 5x + -71 + 8x = 180
Reorder the terms:
4 + -71 + 5x + 8x = 180
Combine like terms: 4 + -71 = -67
-67 + 5x + 8x = 180
Combine like terms: 5x + 8x = 13x
-67 + 13x = 180
Solving
-67 + 13x = 180
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '67' to each side of the equation.
-67 + 67 + 13x = 180 + 67
Combine like terms: -67 + 67 = 0
0 + 13x = 180 + 67
13x = 180 + 67
Combine like terms: 180 + 67 = 247
13x = 247
Divide each side by '13'.
x = 19
Simplifying
x = 19